Child Temperament, Maternal Feeding Practices, and Parenting Styles and Their Influence on Obesogenic Behaviors in Hispanic Preschool Children. (August 2019) - Innella, Nancy; McNaughton, Diane; Schoeny, Michael; Tangney, Christy; Breitenstein, Susan; Reed, Monique; Wilbur, Joellen
Although obesogenic behaviors (physical activity and/or sedentary behavior and dietary intake) are known predictors of childhood weight status, little is known about mother and child behaviors contributing to obesogenic behaviors and obesity in Hispanic preschool children, whose obesity rate is higher than in non-Hispanic Whites and non-Hispanic Blacks. The purpose of this cross-sectional, descriptive study was to examine relationships among child temperament, maternal behaviors (feeding practices and parenting style), child obesogenic behaviors, and child weight status in 100 Hispanic preschool children. Results showed that higher scores on the negative affectivity dimension of child temperament were associated with higher scores on the dimension of permissive parenting, and permissive parenting was associated with less time spent in sedentary behaviors ( B = −3.53, confidence interval [−7.52, −0.90]). Findings can guide school nurses in developing interventions that consider child temperament and parenting style to promote nonobesogenic behavior in Hispanic preschoolers.